Investigation into X-STR haplotype frequencies for forensic human identification in South Africa - Whittaker, Amy-Leigh (Department of Pathology, 2024)
The utilisation of X-chromosome short tandem repeats (X-STRs) for DNA profiling has been demonstrated to be particularly useful in resolving distant familial relations and deficiency paternity testing. The implementation of X-STRs within a medico-legal context requires baseline frequency data for the general population to allow for appropriate statistical interpretations of results. This study aimed to generate the first X-STR data for the South African population andinternally validate the Qiagen Investigator Argus X-12 QS kit. Biological samples from 781 South African individuals (517 males and 264 females) with either African, mixed, European, or Indian/Asian ancestry were processed. Statistical analyses were performed using StatsX and Arlequin. Herein, allele and haplotype frequencies and forensic parameters for the South African population are reported, as well as data related to the reproducibility, sensitivity, limit of detection, and concordance of the Investigator Argus X-12 QS kit. DXS10135 was the most informative locus, while DXS7423 was the least informative locus. The combined power of discrimination for both males and females was greater than 0.999999999. The haplotype diversity of all four linkage groups exceeded 0.993. Linkage group 1 was the most informative, with 421 unique haplotypes. Possible linkage disequilibrium was detected in five loci pairs in male samples and three loci pairs in female samples. However, it is expected that the effects of false linkage disequilibrium were present, and only loci pairs within the same linkage group may be in true linkage disequilibrium. All loci in female samples were in Hardy-Weinberg equilibrium, except DXS10148. Additionally, a total of 59 off-ladder alleles were identified. The discriminatory power of these results suggests X-STRs may be beneficial for forensic casework in South Africa. The availability of this data could allow this method to be used locally to assist with civil inheritance disputes and the identification of unknown individuals.